Killing bin Laden: A Moral Analysis - Strawser, B. author. aut Link
VIII, 79 p. 1 illus.
Keywords: Strawser examines several possible ethical justifications for the killing of Osama bin Laden and finds nearly all of them wanting. One, however, he argues is sound: that bin Laden was liable to be killed as a necessary and proportionate act of defensive harm on behalf of innocent people.